SOME POSSIBILITIES OF THE AERIAL DRONES USE IN PRECISION AGRICULTURE – A REVIEW - IOSIF IOJA; VALENTIN NEDEFF; MARICEL AGOP; FLORIN MARIAN NEDEFF (Journal of Engineering Studies and Research)
Precision agriculture, together with remote sensing and vegetation indices, represents a modern correlation that maximizes efficiency and sustainability in farmland management, contributing to more efficient and responsible production. Remote sensing in agriculture is an important technology that uses data from sensors mounted on satellites, drones, and aircraft to monitor and evaluate agricultural land. Vegetation indices are needed in agricultural remote sensing and precision agriculture because they provide quantitative and objective information on agricultural crops contributing to more efficient, sustainable and cost-effective land management.